Dyke-Davidoff-Masson-Syndrome Manifested by seizures and learning difficulties: A Case Report - Khalil, Mohammad Ibrahim; Hakim, Maliha; Momin, Afzal; Nayeem, Abu; Islam, Md. Mohitul; Das, Priyatosh Chandra (Journal of Shaheed Suhrawardy Medical College, 2013)
Dyke-Davidoff-Masson Syndrome (DDMS), also known as cerebral hemiatrophy, is a rare clinical condition characterized by seizures, facial asymmetry, contralateral spastic hemiplegia or hemiparesis, with learning difficulties and behavioral changes. It is commonly diagnosed in presence of clinical feature associated radiological findings which include cerebral hemiatrophy with homolateral hypertrophy of the skull and sinuses. In this present case report a 12 year old teenager female patient was diagnosed as DDMS with recurrent generalized seizures, learning difficulties and right sided hemiparesis. Magnetic resonance imaging (MRI) of the brain showed hemiatrophy involving the left cerebral hemisphere and EEG showed generalized epileptiform discharged. An X-ray of the paranasal air sinuses was normal. DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20768 J Shaheed Suhrawardy Med Coll 2013;5(2):111-113